Sectoral dual-polarized MIMO antenna for 5G-NR band N77 base station - Muhsin Muhsin; Afina Lina Nurlaili; Aulia Saharani; Indah Rahmawti Utami (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Massive internet of things (IoT) in 5G has many advantages as a future technology. It brings some challenges such as a lot of devices need massive connection. In this case, multiple-input multiple-output (MIMO) systems offer high performance and capacity of communications. There is a challenge of correlation between antennas in MIMO. This paper proposes three-sectors MIMO base station antenna for 5G-New Radio (5G-NR) band N77 with dual polarized configuration to reduce the correlation. The proposed antenna has a maximum coupling of -16.90 dB and correlation below 0.01. The obtained bit error rate (BER) performance is very close to non-correlated antennas with bandwidth of 1.87 GHz. It means that the proposed antenna has been well designed.